2008
DOI: 10.1126/science.1155495
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Genomics Reveals a Single-Species Ecosystem Deep Within Earth

Abstract: DNA from low-biodiversity fracture water collected at 2.8-kilometer depth in a South African gold mine was sequenced and assembled into a single, complete genome. This bacterium, Candidatus Desulforudis audaxviator , composes >99.9% of the microorganisms inhabiting the fluid phase of this particular fracture. Its genome indicates a motile, sporulating, sulfate-reducing, chemoautotrophic thermophile that can fix its own nitrogen and carbon by using machinery shared with archaea. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
451
1
6

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 469 publications
(464 citation statements)
references
References 55 publications
(77 reference statements)
6
451
1
6
Order By: Relevance
“…In addition, besides Desulfohalobium and Desulfotomaculum, sequences affiliated to a Candidatus Desulforudis audaxviator were frequently detected in fluids produced from the cold well. Sequences of Candidatus Desulforudis audaxviator were also found in 60°C tempered fracture water collected from a South African gold mine at a depth of 2.8 km (Chivian et al 2008). Recently, a study by Alawi et al (2011) identified sequences similar to Candidatus Desulforudis audaxviator in 61°C tempered fluid samples taken after heat extraction in the topside facility of a geothermal plant in the Molasse Basin (Germany).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, besides Desulfohalobium and Desulfotomaculum, sequences affiliated to a Candidatus Desulforudis audaxviator were frequently detected in fluids produced from the cold well. Sequences of Candidatus Desulforudis audaxviator were also found in 60°C tempered fracture water collected from a South African gold mine at a depth of 2.8 km (Chivian et al 2008). Recently, a study by Alawi et al (2011) identified sequences similar to Candidatus Desulforudis audaxviator in 61°C tempered fluid samples taken after heat extraction in the topside facility of a geothermal plant in the Molasse Basin (Germany).…”
Section: Discussionmentioning
confidence: 98%
“…were detected in fluids cooled at the heat exchanger from 75°C to 46°C. Physiological characteristics of detected SRB and Halanaerobiaceae correspond to the subsurface environment with respect to optimum temperature, salt concentration, and pH, and are commonly found in similar anaerobic saline environments such as sediments from salt lakes (Cayol et al 1994;Jakobsen et al 2006), geothermal groundwater (Daumas et al 1988), fracture water (Chivian et al 2008), as well as in oil fields and petroleum hydrocarbon contaminated sites (Magot et al 2000;Cayol et al 2002;Denger et al 2002;Bonch-Osmolovskaya et al 2003). Halophilic Desulfohalobium utahense are known moderate halophilic and mesophilic sulfate and thiosulfate reducers that use a broad range of electron donors including various short-chain fatty acids and primary (C 1-5 ) alcohols, amino acids, H 2 /acetate and H 2 /yeast extract (Jakobsen et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, PCR primers for the specific amplification of the large subunit of the [FeFe]hydrogenase gene (hydA) were developed to examine the diversity of hydA as a proxy for fermentative bacteria in a H 2 -generating saline microbial-mat system (Boyd et al, 2009b) and in a H 2 -generating anaerobic bioreactor (Xing et al, 2008). The results of these studies, as well as those from a number of metagenomic investigations that include the deep subsurface (Chivian et al, 2008) and termite hindgut environments (Warnecke et al, 2007), collectively indicate a widespread distribution and diversity of [FeFe]-hydrogenase in nature. However, our understanding of the environmental constraints that control the distribution and diversity of [FeFe]hydrogenase-mediated H 2 production in natural systems is confounded by the tight coupling between H 2 production and consumption and by the abiological reactions that contribute to H 2 production and consumption in natural systems.…”
Section: Introductionmentioning
confidence: 99%
“…Lovley and Chapelle (1995) give a general summary of deep subsurface microbial processes. Chivian et al (2008) provide a schematic illustration of microbial processes in a deep single-species ecosystem, including mineralogic reactions and the radioactive and radiolytic processes that contribute energy and nutrients. Pedersen (1996) provided a review of investigations of bacteria in deep crystalline bedrock and their potential importance for nuclear-waste disposal in underground repositories.…”
Section: Microbial Activity In the Deep Subsurfacementioning
confidence: 99%